A new biological snap oscillator: its modelling, analysis, simulations and circuit design. (2018) - Vaidyanathan, Sundarapandian; Feki, Moez; Sambas, Aceng; Lien, Chang-Hua
In this work, we build a new four-dimensional autonomous biological snap oscillator model for enzyme-substrate reactions in a brain waves model. We investigate the process modelling of the new autonomous biological snap oscillator via phase portraits, simulations, dissipativity, symmetry, Lyapunov exponents, Kaplan-Yorke dimension, bifurcation analysis, Poincaré map, etc. In addition, it is interesting that the electronic circuit model of the new biological snap oscillator is also investigated and phase portraits are analysed in MultiSIM.